Analysis of Crystal Structure and Texture on Al-5052 Rod Processed by ECAP and Post-ECAP Annealing at 100-300 oC - R. Ibrahim Purawiardi; I Nyoman Gede Putrayasa Astawa (University of Muhammadiyah Jakarta, 2020)
Equal-channel angular pressing (ECAP) treatment is a method to improve the mechanical properties of bulk metals without adding or extracting their alloy elements. The ECAP process can improve severe plastic deformation that will increase mechanical properties such as hardness and modulus of elasticity. The disadvantage of ECAP product is non-uniform mechanical properties. To solve this problem, the post-ECAP annealing process can be applied to form more uniform mechanical properties. This phenomena should also be caused by the change of crystal structure and texture during this process. However, the study of the change of crystal structure and texture during ECAP and followed by annealing process was seldom done. This study aims to try to determine the characteristics of crystal structure and texture of ECAPed and post-ECAP-annealed materials with annealing temperature variation of 0, 100, 200, and 300 oC. Four Al-5052 alloy rods were used as material samples. The results of this study show that the annealing process can homogenize the crystal structure of ECAPed Al-5052 rod. On the other hand, the texture characteristics of ECAPed Al-5052 rod become more random as an implication of increasing annealing temperature.